New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus - Galvis, William; Rheims, Cristina Anne (Zootaxa, 2018)
The huntsman spider genus Anaptomecus was proposed by Simon (1903) to include the type species, A. longiventris Simon, 1903, described from a juvenile male collected in Cayambé (San Pedro de Cayambé), Pichincha, Ecuador. Mello-Leitão (1940) described a second species, A. rufescens, from a female collected in Essequibo River, Guyana. The genus remained unstudied until the early 2000’s when Jäger et al. (2009) described the adult male and female of A. longiventris and transferred A. rufescens to Sparianthina Banks, 1929. In this same paper, the authors described A. temii Jäger, Rheims & Labarque, 2009, based on a male from Panama, and A. levyi Jäger, Rheims & Labarque, 2009, based on a female from Colombia. A few years later, Guala et al. (2012), increased the number of known species with the descriptions of A. paru Guala, Labarque & Rheims, 2012 and A. suni Guala, Labarque & Rheims, 2012, both based on males and females from Ecuador. Thus, Anaptomecus currently includes five species and is distributed in southern Central and northern South America, from Costa Rica to central Ecuador (Puerto Napo, Napo) (World Spider Catalog 2018).